Extending the evolution of the stellar mass–size relation at z ≤ 2 to low stellar mass galaxies from HFF and CANDELS. Issue 1 (21st June 2021) - Nedkova, Kalina V; Häußler, Boris; Marchesini, Danilo; Dimauro, Paola; Brammer, Gabriel; Eigenthaler, Paul; Feinstein, Adina D; Ferguson, Henry C; Huertas-Company, Marc; Johnston, Evelyn J; Kado-Fong, Erin; Kartaltepe, Jeyhan S; et al.
ABSTRACT: We reliably extend the stellar mass–size relation over 0.2 ≤ z ≤ 2 to low stellar mass galaxies by combining the depth of Hubble Frontier Fields with the large volume covered by CANDELS. Galaxies are simultaneously modelled in multiple bands using the tools developed by the MegaMorph project, allowing robust size (i.e. half-light radius) estimates even for small, faint, and high redshift galaxies. We show that above 10 7 M⊙, star-forming galaxies are well represented by a single power law on the mass–size plane over our entire redshift range. Conversely, the stellar mass–size relation is steep for quiescent galaxies with stellar masses $\ge 10^{10.3}\, {\rm M}_\odot$ and flattens at lower masses, regardless of whether quiescence is selected based on star-formation activity, rest-frame colours, or structural characteristics. This flattening occurs at sizes of ∼1 kpc at z ≤ 1. As a result, a double power law is preferred for the stellar mass–size relation of quiescent galaxies, at least above 10$^7\, {\rm M}_\odot$ . We find no strong redshift dependence in the slope of the relation of star-forming galaxies as well as of high mass quiescent galaxies. We also show that star-forming galaxies with stellar masses $\ge 10^{9.5}\, {\rm M}_\odot$ and quiescent galaxies with stellar masses $\ge 10^{10.3}\, {\rm M}_\odot$ have undergone significant size growth since z ∼ 2, as expected; however, low mass galaxies have not. Finally, we supplement our data with predominantly quiescent dwarf galaxies from the core of the Fornax cluster, showing that the stellar mass–size relation is continuous below 10$^7\, {\rm M}_\odot$, but a more complicated functional form is necessary to describe the relation.